Liebermannite, KAlSi3O8, a new shock‐metamorphic, high‐pressure mineral from the Zagami Martian meteorite. (30th October 2017) - Ma, Chi; Tschauner, Oliver; Beckett, John R.; Rossman, George R.; Prescher, Clemens; Prakapenka, Vitali B.; Bechtel, Hans A.; MacDowell, Alastair
Abstract: In this paper, we discuss the occurrence of liebermannite (IMA 2013‐128), KAlSi3 O8, a new, shock‐generated, high‐pressure tetragonal hollandite‐type structure silicate mineral, in the Zagami basaltic shergottite meteorite. Liebermannite crystallizes in space group I 4 /m with Z = 2, cell dimensions of a = 9.15 ± 0.14 (1σ) Å, c = 2.74 ± 0.13 Å, and a cell volume of 229 ± 19 Å 3 (for the type material), as revealed by synchrotron diffraction. In Zagami, liebermannite likely formed via solid‐state transformation of primary igneous K‐feldspar during an impact event that achieved pressures of 20 GPa or more. The mineral name is in honor of Robert C. Liebermann, a high‐pressure mineral physicist at Stony Brook University, New York, USA.